Immunoproteomic characterization of Brucella canis to identify proteins candidates as antigens for serodiagnosis - Silva, David Attuy Vey da (2018)
Canine brucellosis is a zoonotic disease, caused by Brucella canis, which is the main cause of abortion and infertility in dogs. This study had the objective to investigate a B. canis outbreak in a breeding kennel, to describe a multistep approach to characterize the B. canis isolates obtained, and to identify B. canis proteins specifically reacting with antibodies from naturally infected dogs. The kennel was located in São Paulo, SP, Brazil. At the time of sampling, in 2014, the kennel comprised 17 adult Pug dogs. Blood samples were used both to isolate the bacteria and to detect Brucella spp. DNA by the polymerase chain reaction. Serum samples were used to detect antibodies against B. canis using an immunocromatographic test, the rapid slide agglutination test with or without 2-mercaptoethanol and two ELISA kits. The Brucella isolates were characterized through the classical bacteriological tests, mass spectrometry and whole genome sequencing. The total protein content of Brucella isolates was extracted and separated using one and two-dimension polyacrylamide gel electrophoresis (1D and 2D, respectively), and then tested against sera collected from bacteremic, non-bacteremic and non-B. canis infected dogs using western immunoblotting. The reacting protein spots were identified using matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS). Vaginal discharge, abortion, stillbirth, conception failure and general lymphadenopathy were the clinical signs found in the infected dogs. Gram-negative, coccoid rod-shaped bacteria were isolated from 24 blood samples. Antibodies against B. canis were detected in all dogs at least once by the performed serological tests. Mass spectrometry analysis assigned all isolates to the genus Brucella. The phenotypic data clearly identified the isolates as B. canis with only slight differences in phage typing patterns. The 2D separated protein spots were identified by MALDI-TOF MS as 93 different proteins, out of them, 19 were identified in infected dogs (during the bacteremic and non-bacteremic phases of the infection) and were not identified in non-infected dogs. These proteins have the potential to be used as antigens in serological tests in an attempt to improve the diagnosis of the infection, since a reliable diagnosis is an essential measure for the control and prevention of canine brucellosis. The multistep approach using classical microbiological methods, mass spectrometry and whole genome sequencing allowed the characterization of the B. canis with high discriminatory power, which may be useful for outbreak investigations.